Tube Feeding and Advanced Progressive Dementia - Post, Stephen G. (The Hastings Center report, 2001)
Tube feeding is often presented as a nearly risk free and beneficial treatment for patients with dementia. But evidence shows that its benefits are illusory, while its risks are greater than many realize. Assisted oral feeding and good hospice care are better options.